Data from: Convergent evolution of the ladder-like ventral nerve cord in Annelida - Helm, Conrad; Beckers, Patrick; Bartolomaeus, Thomas; Drukewitz, Stephan H.; Kourtesis, Ioannis; Weigert, Anne; Purschke, Günter; Worsaae, Katrine; Struck, Torsten H.; Bleidorn, Christoph (Dryad, 2019)
Background: A median, segmented, annelid nerve cord has repeatedly been
compared to the arthropod and vertebrate nerve cords and became the most
used textbook representation of the annelid nervous system. Recent
phylogenomic analyses, however, challenge the hypothesis that a
subepidermal rope-ladder-like ventral nerve cord (VNC) composed of a
paired serial chain of ganglia and somata-free connectives represents
either a plesiomorphic or a typical condition in annelids. Results: Using
a comparative approach by combining phylogenomic analyses with
morphological methods (immunohistochemistry and CLSM, histology and TEM),
we compiled a comprehensive dataset to reconstruct the evolution of the
annelid VNC. Our phylogenomic analyses generally support previous
topologies. However, the so far hard-to-place Apistobranchidae and
Psammodrilidae are now incorporated among the basally branching annelids
with high support. Based on this topology we reconstruct an intraepidermal
VNC as the ancestral state in Annelida. Thus, a subepidermal ladder-like
nerve cord clearly represents a derived condition. Conclusions: Based on
the presented data, a ladder-like appearance of the ventral nerve cord
evolved repeatedly, and independently of the transition from an
intraepidermal to a subepidermal cord during annelid evolution. Our
investigations thereby propose an alternative set of neuroanatomical
characteristics for the last common ancestor of Annelida or perhaps even
Spiralia.
Assembled dataset_MARE_1.5 analysisAssembled molecular dataset underlying
the MARE 1.5 analysis.Neurophyl_Matrix_MARE_15.fasAssembled dataset_MARE_2
analysisAssembled datatset underlying the MARE 2
analysis.Neurophyl_Matrix_MARE_2.fas
Keywords: neurophylogeny; Lophotrochozoa; Spiralia; segmentation; Neuroanatomy